Reading is my window: books and the art of reading in women's prisons - Sweeney, Megan (University of North Carolina Press, 2010)
Tell me what you read; I will tell you what you are : reading and education in U.S. penal history -- The underground book railroad : material dimensions of reading -- Between a politics of pain and a politics of pain's disavowal -- Fear of books : reading urban fiction -- To set the captives free : self-help reading practices -- Encounters : the meeting ground of books -- Conclusion. This really isn't a rehabilitation place : policy considerations